Taxonomic study of oribatid mites (Acari, Oribatida) of Bi Dup—Nui Ba National Park (southern Vietnam) - Ermilov, Sergey G.; Anichkin, Alexander E. (Zootaxa, 2014)
A list of oribatid mite taxa from six localities of Bi Dup—Nui Ba National Park (southern Vietnam) is provided. It includes 89 species/subspecies, 68 genera, and 40 families, of these 23 species, two subgenera, 15 genera and seven families are recorded for the first time in Vietnam. Three species (Elaphoppia quadripilosa, Exoribatula cf. longior, Allogalumna (Allogalumna) rotundiceps), one subgenus (Lohamnnia (Carolohmannia) and one genus (Elaphoppia) are recorded for the first time in the Oriental region. Fourteen new species, Lohmannia (Carolohmannia) monosetosa sp. nov., Tectodamaeus heterotrichus sp. nov., Allosuctobelba vietnamensis sp. nov., Epieremulus bidupensis sp. nov., Dolicheremaeus insolitus sp. nov., Fissicepheus striganovae sp. nov., Tegeocranellus martinezi sp. nov., Anachipteria svetlanae sp. nov., Indoribates (Indoribates) bicarinatus sp. nov., Peloribates tatyanae sp. nov., Neoribates (Neoribates) monodactylus sp. nov., Allogalumna (Allogalumna) paramachadoi sp. nov., Galumna (Neogalumna) longilineata sp. nov., G. (N.) tolstikovi sp. nov., are described. The taxonomic status of the two galumnid genera, Neogalumna and Globogalumna, is discussed: Neogalumna is proposed as the subgenus Galumna (Neogalumna) stat. nov.; Globogalumna is proposed as the subgenus Allogalumna (Globogalumna) stat. nov. An identification key to the known species of Galumna (Neogalumna) is given.